Enhancing Women's Graduate Education: Workshopping Women's Socialization to the Academic Profession - Sheffield, Suzanne (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article outlines the impact of a professional development workshop, Women in Academe, arguing that it offers a first step in addressing a crucial gap in graduate students' education. Workshop participants' feedback confirms the usefulness of providing opportunities for discussion and strategizing to enhance women's career success in the academy.